The Satisfaction of Chinese Learners towards Thai and Native Instructors of Chinese Language - Predeepoch, Teeraparp; Khaowbanpaew , Kanlaya (Journal of Sinology (วารสารจีนวิทยา), 2015)
The objectives of this research are 1. To study, analyze and compare the satisfaction of undergraduate students towards Thai and native Chinese instructors who are teaching Chinese which consist of groups of subjects, teaching method, levels and languages used for teaching. 2. To study the satisfaction of undergraduate students towards Thai and native Chinese instructors who are teaching Chinese in term of their strength and weakness. The samples of the study are 180 senior Chinese department students from Mae Fah Luang University, Chiang Rai Rajabhat University, Chiang Mai University and University of Phayao by using questionnaire as the data gathering instrument. Percentage, Mean, and Standard Deviation are applied for data analysis.